2014
DOI: 10.4103/0976-237x.132301
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and histopathological changes in palatal mucosa following two treatment modalities in patients wearing maxillary complete dentures with suction cup

Abstract: Aim:The aim of the study was to determine the clinical and histopathological effect on palatal hyperplasia caused by suction cups by different methods of management used for recovery of abused tissues.Materials and Methods:A total of 35 subjects agreed for biopsy procedure, from 50 patients who gave consent for the study. Out of the 35 subjects, 20 were randomly selected for treatment with discontinuation of denture (Group I) and 15 selected for denture relined with tissue conditioner (COE-comfort) (Group II).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
0
4
0
1
Order By: Relevance
“…Zastosowanie cienkiej folii cynowej dokładnie zaadoptowanej do modelu zapewnia idealną gładkość wewnętrznej, niepolerowanej strony uzupełnienia a wprasowywany akrylan jest dobrze skondensowany przy folii dzięki czemu eliminuje się czynnik drażniący wynikający często z mikroporowatości gipsowego modelu. 16,17 W przypadku zmian rozlanych, rozległych, niepoddających się leczeniu zachowawczemu, należy wprowadzić metody inwazyjne w celu usunięcia przerośniętej błony śluzowej przed wykonaniem nowej protezy. Stosuje się techniki inwazyjne, takie jak: klasyczne wycięcie zmiany, mechaniczna abrazja błony śluzowej poprzez starcie szybkoobrotowym narzędziem skrawającym, elektrochirurgia, krioterapia i laseroterapia.…”
Section: R Koczorowski I Inniunclassified
“…Zastosowanie cienkiej folii cynowej dokładnie zaadoptowanej do modelu zapewnia idealną gładkość wewnętrznej, niepolerowanej strony uzupełnienia a wprasowywany akrylan jest dobrze skondensowany przy folii dzięki czemu eliminuje się czynnik drażniący wynikający często z mikroporowatości gipsowego modelu. 16,17 W przypadku zmian rozlanych, rozległych, niepoddających się leczeniu zachowawczemu, należy wprowadzić metody inwazyjne w celu usunięcia przerośniętej błony śluzowej przed wykonaniem nowej protezy. Stosuje się techniki inwazyjne, takie jak: klasyczne wycięcie zmiany, mechaniczna abrazja błony śluzowej poprzez starcie szybkoobrotowym narzędziem skrawającym, elektrochirurgia, krioterapia i laseroterapia.…”
Section: R Koczorowski I Inniunclassified
“…Total denture retention is a dynamic phenomenon, involving several variables. It has been found that objective and chewing ability were primarily influenced by denture retention or stability [3], [4].…”
Section: Introductionmentioning
confidence: 99%
“…Whether this is by covalent bonds or chelation, the idea is a fixed molecular relationship and the fact that there is a separation resistance is called adhesion regardless of the inability to define a particular mechanism [7]. The use of suction cups in maxillary denture satisfies retention and stability requirements [4]. It has been found that the suction cup liner can be applied to both the upper and lower dentures.…”
Section: Introductionmentioning
confidence: 99%
“…The lesions are usually nodular and firm, with color varying from pink to red [ 1 ]. These lesions are usually induced by negative pressure between the tissue and ill-adapted denture or in vacuum chamber used in the upper denture [ 3 ]. Vacuum chambers consist in a palatal relief in the denture.…”
Section: Introductionmentioning
confidence: 99%
“…At first, the chamber creates negative pressure in the area, enhancing retention [ 4 ]. However, with time, the negative pressure causes an inflammatory papillary hyperplasia, being painless and taking the form of its chamber [ 3 ]. It can also be associated with the colonization of Candida albicans , causing denture stomatitis and angular cheilitis [ 5 ].…”
Section: Introductionmentioning
confidence: 99%